Revision of Agelopsis (Coleoptera: Chrysomelidae: Galerucinae) - Bezděk, Jan (Zootaxa, 2020)
The genus Agelopsis Jacoby, 1896 is redefined and revised. Zizonia Chen, 1976 and Liroetinus Lopatin, 2004 are proposed as new synonyms of Agelopsis. Nine species of Agelopsis are recognized: A. aeneoviridis (Lopatin, 2004) (comb. nov.) (China: Sichuan), A. belousovi (Lopatin, 2004) (comb. nov.) (China: Sichuan, Yunnan), A. caeruleus Jacoby, 1896 (Nepal, India: Jharkhand, West Bengal), A. metallicus (Bryant, 1954) (comb. nov.) (Myanmar), A. spinipes (Ogloblin, 1936) (comb. nov.) (China: Gansu, Sichuan), A. tibetanus (Chen, 1976) (comb. nov.) (China: Xizang), A. konstantinovi sp. nov. (China: Shaanxi, Sichuan), A. malaisei sp. nov. (Myanmar, China: Yunnan) and A. traxlerorum sp. nov. (China: Yunnan). Colour photos of habitus and aedeagi as well as drawings of female genitalia are presented.